ANALISIS RESIDU PESTISIDA KARBAMAT JENIS KARBARIL DAN KARBOFURAN PADA BIJI KEDELAI PASCA PANEN - Djarot Sugiarso; Tikto Priharnomo (The East Java Biological Society, 1996)
There are 2 methods for separating the pesticide by extraction. The first (solid method) use 3 organics solvent: acetonitriil, Petrolium ether, and Dichloromethane, and the second (alternative method) use 2 organic solvent, there are Dichloromehane and Petrolium ether. These two methods was compared in order to know which one is usable to detect the pesticide residue in soybean. The concentration of the carbary residu for the first method was 0.0302 ppm. In the second one the residu that found still lower from limit of ADI that patent by WHO : 0.1 pm and the residu carbufuran undetectioned. The result, showed that the second method can't be used as alternative method.